22 Study the Immune Response of Conjunctival and Subcutaneous Vaccination of Goats with RB51 Vaccine for Controlling Brucellosis: Waffa Abdulelah Ahmad1@; Ayad Ibrahim Haiaef and Sufian Saleh Salman2 - Ahmad1, Waffa Abdulelah (The Iraqi Journal of Veterinary Medicine, 2013)
This study was conducted to evaluate the efficacy of RB51 vaccine in immunization of goats against brucellosis although it is a specific vaccine for cattle, fifteen pregnant and non-pregnant goats were divided into three groups, 5 goats were injected subcutaneously(S/C) with 2 mls of RB51 vaccine which contain 4 × 108 CFU , 5 goats were vaccinated through conjunctival route (C/J) with 0.2 ml of RB51 which contain 4 × 108 CFU , and the last 5 goats were injected with PBS and kept as control group. It has been ascertained that no abortion occurred in the vaccinated animals except one case of a weak kid was born in S/C vaccinated group. Humeral immune response for the vaccinated animals measured by serological test (Rose Bengal and Passive hemagglutination tests) every two weeks, while the cellular immune response measured by brucellin test at the 6th week. Passive haemaglutination test (PHA) was positive and the antibodies were increased significantly (P<0.05) at the 2nd week to reach 10.4±2.4 and 6.4±0.9 in S/C and C/J routes respectively, and increased significantly (P<0.05) at 8th week to reach 38.4±6.4 and 22.4±3.9 in S/C and C/J routes respectively, and decreased significantly at 12th week which reach 9.6±1.6 to 6.4±0.9. Brucellin from RB51 strain prepared to be used as antigen in the PHA test and also in skin test to determine delayed type hypersensitivity, serial dilutions of RB51 brucellin had been done to confer the optimal concentration in skin test that did not induce toxicity for mice 40µg was the optimal concentration that has been given to goats. In goats the results indicated that the S/C group showed a high delayed type hypersensitivity compared with C/J group and the good skin reactions was increased to reach the maximum at 48 hrs post brucellin injection (PBI), when the erythema diameter reached 7.1±0.09mm and 5.4±0.3mm in S/C and C/J groups respectively and skin thickness was2.9±0.1 mm and 2.1±0.2 mm in S/C and C/J groups respectively. These results showed that immunized animals expressed cellular and humeral immune response examined by DTH and PHA. Concluded that the RB51 vaccine gave good level of immunization in goats and it can be considered as alternative vaccine against heterogonous Brucella spp.